Efficacy and safety of 3-month versus 6-month oxaliplatin-based adjuvant chemotherapy in colorectal cancer: a systematic review and meta-analysis - Wu, Haiqiong; Li, Jun; Miao, Jidong; Li, Jiawei (Frontiers in Oncology, 2026)
BackgroundThe optimal duration of oxaliplatin-based adjuvant chemotherapy for stage II–III colorectal cancer (CRC) remains uncertain. Although a 3-month regimen may reduce toxicity, particularly peripheral sensory neuropathy (PSN), its effect on long-term survival is unclear. This study systematically compared the efficacy and safety of 3 versus 6 months of oxaliplatin-based adjuvant chemotherapy in stage II–III CRC patients.MethodsA systematic search of PubMed, Embase, the Cochrane Library, and Web of Science was conducted to identify randomized controlled trials (RCTs) comparing 3 months versus 6 months FOLFOX or CAPOX adjuvant chemotherapy in stage II–III CRC patients. Outcomes included disease-free survival (DFS), 3-year DFS rate, overall survival (OS), chemotherapy completion rate, and PSN. The certainty of evidence was evaluated using the GRADE approach, and trial sequential analysis (TSA) was performed to assess the robustness of the results.ResultsSix RCTs involving a total of 16,420 stage II–III CRC patients were included. In the overall patients, the 3-month regimen showed no significant difference in DFS compared with the 6-month regimen (HR = 1.05, 95% CI 0.98–1.13, P = 0.18). Within the FOLFOX subgroup, the risk of DFS events was increased in the 3-month regimen (HR = 1.21, 95% CI 1.11–1.33, P < 0.001), with a similar difference observed among stage III patients (HR = 1.23, 95% CI 1.06–1.43, P = 0.007). No significant differences were observed in OS or 3-year OS rate, and all subgroup analyses showed no statistically significant differences in 3-year DFS rates. The 3-month regimen demonstrated a significantly higher chemotherapy completion rate, and grade 3–4 PSN was significantly lower in the 3 months regimen.ConclusionStage II patients may preferentially receive a 3-month treatment regimen, whereas stage III patients receiving FOLFOX should still consider a 6-month regimen.Systematic Review Registrationhttps://inplasy.com/inplasy-2025-12-0022/, identifier INPLASY-2025-12-0022.